2021
DOI: 10.1016/j.celrep.2021.109749
|View full text |Cite
|
Sign up to set email alerts
|

An ancient RAB5 governs the formation of additional vacuoles and cell shape in petunia petals

Abstract: An ancient RAB5 governs the formation of additional vacuoles and cell shape in petunia petals Graphical abstract Highlights d Flowering plants contain three ancient classes of canonical RAB5 proteins d RAB5s display divergent transcription regulation and intracellular localization d RAB5a is specifically required to form vacuolinos from small endosomal precursors d The others, RAB5a1 and RAB5a2, cannot functionally replace RAB5a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The ability to identify and isolate new mutations is largely affected by how difficult it is to spot the new phenotype. Among the new mutants emerging in the collection, the easiest to spot are those heavily affecting the plant architecture and those affecting the biosynthetic pathway of anthocyanins and co-pigments such as flavonols (both structural and regulatory genes) ( van Houwelingen et al., 1998 ) (see Figure 1A ); the hyper-acidification of the lumen of the vacuoles where the pigments are stored (also structural and regulatory genes) ( Spelt et al., 2000 ; Quattrocchio et al., 2006 ; Verweij et al., 2008 ; Faraco et al., 2014 ; Verweij et al., 2016 ); the formation of additional vacuoles ( Faraco et al., 2017 ); and the shape and dimension of the cells ( Li et al., 2021 ). Many genes involved in these processes were identified through mutants that appeared spontaneously in progeny of W138 and derived lines.…”
Section: Regulation Of Pigmentation and Related Processes In ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to identify and isolate new mutations is largely affected by how difficult it is to spot the new phenotype. Among the new mutants emerging in the collection, the easiest to spot are those heavily affecting the plant architecture and those affecting the biosynthetic pathway of anthocyanins and co-pigments such as flavonols (both structural and regulatory genes) ( van Houwelingen et al., 1998 ) (see Figure 1A ); the hyper-acidification of the lumen of the vacuoles where the pigments are stored (also structural and regulatory genes) ( Spelt et al., 2000 ; Quattrocchio et al., 2006 ; Verweij et al., 2008 ; Faraco et al., 2014 ; Verweij et al., 2016 ); the formation of additional vacuoles ( Faraco et al., 2017 ); and the shape and dimension of the cells ( Li et al., 2021 ). Many genes involved in these processes were identified through mutants that appeared spontaneously in progeny of W138 and derived lines.…”
Section: Regulation Of Pigmentation and Related Processes In ...mentioning
confidence: 99%
“…The reason for this is that the gene for one of the two pumps was lost from the Arabidopsis genome ( Li et al., 2016 ). Similarly, Arabidopsis is not useful for studying the mechanism for the formation of acidic additional vacuoles (vacuolinos) in specialized tissues ( Faraco et al., 2017 ) because the small GTPase RAB5a, a key player in the formation of these organelles, is absent from the RAB5 subgroup of Brassicaceae ( Li et al., 2021 ).…”
Section: Regulation Of Pigmentation and Related Processes In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notochord vacuoles are proposed to be lysosome-related organelles, and their formation requires the Golgi apparatus as well as endolysosomal trafficking and targeting machinery (Ellis et al, 2013a). It has been suggested that the pre-vacuoles bear a resemblance to “vacuolinos,” a recently discovered type of organelle in plants, which fuse to the tonoplast, a semipermeable membrane surrounding the main plant cell vacuole (Li et al, 2021). The fusion of the notochord pre-vacuoles therefore represents a key membrane contact event during notochord biogenesis (Vassileva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A related complex (MBWW) containing AN1, AN11, the MYB protein PH4 and the WRKY protein PH3 activate downstream genes, PH1 and PH5 , encoding vacuolar P-ATPase that acidify the vacuolar lumen conferring a reddish violet petal color. The same MBWW complex activates genes, including PH1 and a small Rab5a GTPase , involved in the formation of vacuolinos, which are small (1-10 μm) vacuoles that coexist with the large central vacuole (CV) where anthocyanins are stored 9 and act as intermediate stations for newly synthesized vacuolar proteins on their way to the CV 9,10 . Interestingly, this complex is required for stability of the anthocyanins in the central vacuole, as inactivation of MBWW triggers “fading” of the petal color.…”
Section: Introductionmentioning
confidence: 99%